2023
DOI: 10.1037/stl0000261
|View full text |Cite
|
Sign up to set email alerts
|

Structured peer mentoring improves academic outcomes and complements project-based learning in an introductory research methods and statistics course.

Abstract: The present study explored the benefits of peer mentoring as part of a student-centered approach to the teaching of an undergraduate Research Methods and Statistics (RMS) course in Psychology. In the first semester of the study, one section of the RMS course was taught with the inclusion of a peer mentor intervention in the classroom, while the other section was taught without peer mentors (standard). Curriculum and evaluation were the same in both sections. During the second semester of the study, both sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…In addition, employed peer mentors tend to be closer in age to the students; A relatable, welltrained mentor can assist students with improving their academic performances, information retention, and application of knowledge both inside and outside of examinations (Pilot et al, 2021). Given that mentors are often closer to students in age, they can form close relationships with students and make mentees feel more comfortable in seeking help.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, employed peer mentors tend to be closer in age to the students; A relatable, welltrained mentor can assist students with improving their academic performances, information retention, and application of knowledge both inside and outside of examinations (Pilot et al, 2021). Given that mentors are often closer to students in age, they can form close relationships with students and make mentees feel more comfortable in seeking help.…”
Section: Resultsmentioning
confidence: 99%
“…According to Leidenfrost et al (2014), there was a significant difference among students with peer mentors as compared to the ones without a peer mentor in the overall grade the students received after two years; the peer-mentees received lower average grades, demonstrating better performance. In addition, Pilot et al (2021), found that psychology students with peer mentors had higher grades than they did during a semester without peer mentor intervention. Together, these findings suggest that proactive interventions in the first semester of the first year can enhance important aspects of learning and increase success for undergraduate psychology students.…”
Section: Assessments and Measuresmentioning
confidence: 99%
“…According to Leidenfrost et al (2014), there was a significant difference among students with peer mentors as compared to the ones without a peer mentor in the overall grade the students received after two years; the peer-mentees received lower average grades, demonstrating better performance. In addition, Pilot et al (2021), found that psychology students with peer mentors had higher grades than they did during a semester without peer mentor intervention. Together, these findings suggest that proactive interventions in the first semester of the first year can enhance important aspects of learning and increase success for undergraduate psychology students.…”
Section: Assessments and Measuresmentioning
confidence: 99%
“…In addition, employed peer mentors tend to be closer in age to the students; A relatable, welltrained mentor can assist students with improving their academic performances, information retention, and application of knowledge both inside and outside of examinations (Pilot et al, 2021). Given that mentors are often closer to students in age, they can form close relationships with students and make mentees feel more comfortable in seeking help.…”
mentioning
confidence: 99%